2017
DOI: 10.3348/kjr.2017.18.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Hepatocellular Carcinoma with Gadoxetic Acid-Enhanced MRI: 2016 Consensus Recommendations of the Korean Society of Abdominal Radiology

Abstract: Diagnosis of hepatocellular carcinoma (HCC) with gadoxetic acid-enhanced liver magnetic resonance imaging (MRI) poses certain unique challenges beyond the scope of current guidelines. The regional heterogeneity of HCC in demographic characteristics, prevalence, surveillance, and socioeconomic status necessitates different treatment approaches, leading to variations in survival outcomes. Considering the medical practices in Korea, the Korean Society of Abdominal Radiology (KSAR) study group for liver diseases h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 111 publications
0
18
0
Order By: Relevance
“…HCC was diagnosed by surgical resection or liver transplantation in 37 patients and biopsy in 5 patients. In the remaining patients, the diagnosis of HCC was based on the radiological hallmarks of AASLD, or the Korean Liver Cancer Study Group-National Cancer Center Korea (KLCSG-NCC), namely the arterial enhancement and washout on the portal venous or transitional phases ( 8 6 11 12 ). HCCs smaller than 1 cm were diagnosed based on the imaging findings in the same manner according to the KLCSG-NCC guidelines ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…HCC was diagnosed by surgical resection or liver transplantation in 37 patients and biopsy in 5 patients. In the remaining patients, the diagnosis of HCC was based on the radiological hallmarks of AASLD, or the Korean Liver Cancer Study Group-National Cancer Center Korea (KLCSG-NCC), namely the arterial enhancement and washout on the portal venous or transitional phases ( 8 6 11 12 ). HCCs smaller than 1 cm were diagnosed based on the imaging findings in the same manner according to the KLCSG-NCC guidelines ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion restriction, mosaic architecture, nodule-in-nodule appearance, and rim enhancement can be suggested as ancillary imaging findings of HCC (518). However, arterial hyperenhancement and portal or delayed wash-out are the most important imaging characteristics based on the unique histopathological features of HCC, which is increased unpaired arterial blood flow with decreased portal flow during hepato-carcinogenesis (719).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study reported that the utility of unenhanced CT images was improved with the detection of arterial hyperenhancement of HCC (8). Therefore, the definition of arterial enhancement for HCC diagnosis in CT images should be established differently unlike current clinical guidelines (12345) due to insufficient identification rate of arterial enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations